Conflict resolution and forgiveness in the child’s psychological well- being; Experimenting with Forgive Freely animated film - Blessing, Adjeketa (Pedagogika Społeczna Nova, 2024)
Over the years, animated films have always captured the interest of people, especially, young ones, irrespective of ethnicity, or religion. Like many other media, animated films have themes that are capable of posing positive or negative effects on their consumers. They are a common commodity in many households around the world. Hardly any household exists who would deny having seen one. However, its role in conflict resolution, forgiveness, and the child’s psychological wellness is under-researched, especially in Nigeria. Using Alfred Adler’s individual psychology theory developed by Rudolf Dreikurs, This study examined the conflict resolution methods children and parents employed in resolving conflict among children. 107 households comprising 221 children were exposed to lesson 11, Forgive Freely of the Become Jehovah’s Friend Animated Film series for 30 days. After this, resolved conflicts and for- giveness were examined concerning the child’s psychological well-being. For a better understanding of the context, the synopsis of lesson 11, Forgive Freely was presented and briefly analysed. Responds to each of the questions used were presented in analytical tables. The descriptive method of data analy- sis was used to analyse the data collected. Percentages and frequencies were used to evaluate the responses collected from the respondents. The conclusion was drawn based on the percentage ratio. The study finds that conflicts arise among children every day but the relationship between animated films (Forgive Freely), conflict resolution, and forgiveness is insignificant. However, there is a significant relationship between resolved conflict, forgiveness, and psychological well-being. Parental intervention in child conflict is emphasised over that of the animated film genre.